2007
DOI: 10.1111/j.1462-2920.2007.01404.x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic capacity of Bacillus cereus strains ATCC 14579 and ATCC 10987 interlinked with comparative genomics

Abstract: Bacillus cereus is an important food-borne pathogen and spoilage organism. In this study, numerous phenotypes and the genomes of B. cereus strains ATCC 14579 and ATCC 10987 were analysed to compare their metabolic capacity and stress resistance potential. The growth performance of the two strains was assessed for nearly 2000 phenotypes, including use of nutrient sources, performance in acid and basic environments, osmo-tolerance and antibiotic resistance. Several food-relevant phenotypic differences were found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
45
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 45 publications
2
45
0
1
Order By: Relevance
“…To test this idea, we employed a PM analysis to screen for phenotypes associated with the ⌬7ECF and ⌬MWX strains. PM analysis is a high-throughput approach to screen for novel phenotypic traits linked to genetic alterations (8,38,47). Our PM tests included 960 assays for carbon, nitrogen, phosphorus and sulfur source utilization, nutrient stimulation, and pH and osmotic stresses and 240 assays for chemical sensitivities.…”
Section: Resultsmentioning
confidence: 99%
“…To test this idea, we employed a PM analysis to screen for phenotypes associated with the ⌬7ECF and ⌬MWX strains. PM analysis is a high-throughput approach to screen for novel phenotypic traits linked to genetic alterations (8,38,47). Our PM tests included 960 assays for carbon, nitrogen, phosphorus and sulfur source utilization, nutrient stimulation, and pH and osmotic stresses and 240 assays for chemical sensitivities.…”
Section: Resultsmentioning
confidence: 99%
“…The genomic DNA sequences of Bacillus cereus strains ATCC 10987 and ATCC 14579 (nonpathogenic, biosafety level 1 strains) have been published (32). Genomic analysis indicated that B. cereus ATCC 10987 is more similar to Bacillus anthracis Ames than to B. cereus ATCC 14579 (19,29,32). In addition, nine more Bacillus cereus genomes of pathogenic and nonpathogenic strains have been sequenced (GenBank genome database).…”
mentioning
confidence: 99%
“…From this perspective, comparative transcriptomic analysis has been a powerful tool for exploring the metabolic variability in both eukaryotic and prokaryotic organisms (47). Recently, direct high-throughput assessment of phenotypes (phenome) using the Phenotype MicroArray (PM) system (Biolog) (9) has stirred much attention for molecular biology, genomic, and population studies of microorganisms (14,20,29,33,34,37,45,46).…”
mentioning
confidence: 99%